Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2298/fil1706729b
|View full text |Cite
|
Sign up to set email alerts
|

Some common fixed point theorems for tangential generalized weak contractions in metric-like spaces

Abstract: In this paper we define the tangential property in partial metric spaces and metric-like spaces to prove some common fixed point theorems for two pairs of generalized weakly contractions, some examples are given to illustrate ours results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Banach provided the first fixed point theorem in complete metric spaces, which was generalized in different fields, and one of these generalizations was given by Berinde [1], where he introduced the concept of quasicontraction as a generalization of the weak contraction, in the sense of Berinde. Subsequently, several results were obtained, for example, see [2,3,4,19]. Recently, Babu et al [5] introduced a contractive condition, namely "condition (B)", and they proved important results of a fixed point for this contractive condition mappings, similarly, Ćirić et al [6] introduced the concept of generalized quasi-contraction condition and shown some results of existence of fixed point in ordered metric spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Banach provided the first fixed point theorem in complete metric spaces, which was generalized in different fields, and one of these generalizations was given by Berinde [1], where he introduced the concept of quasicontraction as a generalization of the weak contraction, in the sense of Berinde. Subsequently, several results were obtained, for example, see [2,3,4,19]. Recently, Babu et al [5] introduced a contractive condition, namely "condition (B)", and they proved important results of a fixed point for this contractive condition mappings, similarly, Ćirić et al [6] introduced the concept of generalized quasi-contraction condition and shown some results of existence of fixed point in ordered metric spaces.…”
Section: Introductionmentioning
confidence: 99%